Harper's Illustrated Biochemistry - Murray, Robert K Rodwell, Victor W (Mc Graw-Hill, 2003)
UP TO DATE, SUCCINCT, AND MEDICALLY RELEVANT Harper's Biochemistry offers concise yet authoritative coverage of the principles of biochemistry and molecular biology. "Not only is this an excellent text on biochemistry, it also gives you the essentials in molecular biology. The book has excellent illustrations and even focuses on many clinical aspects." *online student review of the 25th edition *Reflects the significant advances in biochemistry that are important to medicine *Includes new chapters on amino acids and peptides, primary structure of proteins, and the Human Genome Project *New and expanded coverage of the mechanisms of action of enzymes, receptors involved in lipoprotein metabolism and reverse cholesterol transport, RNA synthesis, gene regulation, molecular mechanisms of hormone action, and pharmacogenomics *Includes clinical correlations and chapter summaries *More than 500 clear, descriptive illustrations.